Constructing an image of the United States in the British and French editorials about WikiLeaks. Issue 2 (3rd July 2018) - Pjesivac, Ivanka; Luther, Catherine A.; Imre, Iveta
ABSTRACT: In today's globalised world a country's image is an important consideration because it can influence that country's politics and economy (Shimko 1991. Images and Arms Control: Perceptions of the Soviet Union in the Reagan Administration . Ann Arbor: University of Michigan Press; Viosca Jr., Blaise, and Balsmeier. 2005. 'Country Equity: South Africa, a Case in Point.' Journal of Promotion Management 12 (1): 85–95). Scholars have noted that the news media are considered to be major players in creating national images and swaying public perception of foreign countries (Entman, 2008. 'Theorizing Mediated Public Diplomacy: The U.S. Case.' The International Journal of Press/Politics 13 (2): 87–102; Wanta, Golan, and Lee. 2004. 'Agenda Setting and International News: Media Influence on Public Perceptions of Foreign Nations.' Journalism and Mass Communication Quarterly 81: 364–377). The present study examined United States' image typologies in news editorials in Britain and France. Using image theory as a theoretical foundation, this present study employed in-depth qualitative thematic analysis of editorials in The Guardian and Le Monde covering the release of classified U.S. diplomatic cables by WikiLeaks. The overarching U.S. image revealed by editorials did not exactly fit in with the normative images of ally, enemy, complex, imperialist, and colonial/dependent. It did, however, approach the complex image that entailed elements of the ally and imperial image.